Respiratory manifestations of panic disorder in animals and humans: A unique opportunity to understand how supramedullary structures regulate breathing - Kinkead, Richard; Tenorio, Luana [UNESP]; Drolet, Guy; Bretzner, Frederic; Gargaglioni, Luciane (Elsevier B.V., 2014)
The control of breathing is commonly viewed as being a "brainstem affair". As the topic of this special issue of Respiratory Physiology and Neurobiology indicates, we should consider broadening this notion since the act of breathing is also tightly linked to many functions other than close regulation of arterial blood gases. Accordingly, "non-brainstem" structures can exert a powerful influence on the core elements of the respiratory control network and as it is often the case, the importance of these structures is revealed when their dysfunction leads to disease. There is a clear link between respiration and anxiety and key theories of the psychopathology of anxiety (including panic disorders; PD) focus on respiratory control and related CO2 monitoring system. With that in mind, we briefly present the respiratory manifestations of panic disorder and discuss the role of the dorso-medial/perifornical hypothalamus, the amygdalar complex, and the periaqueductal gray in respiratory control. We then present recent advances in basic research indicating how adult rodent previously subjected to neonatal stress may provide a very good model to investigate the pathophysiology of PD. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Control of breathing; Panic disorder; Chemoreflex; Hypercapnic response